Games as Texts : A Practical Application of Textual Analysis to Games - Cole, Alayna M.; Barker, Dakoda (Boca Raton : CRC Press, 2020)
Games as Texts provides an overview and practical steps for analysing games in terms of their representations of social structures, class, power, race, sexuality, gender, animals, nature, and ability. Each chapter applies a traditional literary theory to the narrative and mechanics of games and explores the social commentary the games encourage. This approach demonstrates to players, researchers, games media, and non-gamers how they can engage with these cultural artefacts through both critical reading and theoretical interpretations. Key Features: Explores games through various literary and theoretical lenses Provides exemplar analysis and guiding questions to help readers think critically about games Highlights the social commentary that all texts can reveal--including games--and how this impacts narrative and mechanics
OCLC-licensed vendor bibliographic record.
Keywords: Computer games -- Social aspects; COMPUTERS / Computer Graphics / Game Programming & Design; COMPUTERS / Computer Science